Shkola: problemy perestroiki . Shkola: problemy perestroiki . School: Problems of Perestroika . Школа: проблемы перестройки - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Discussion of the difficulties in implementing education reforms. Featured in the program: Niiazov, Saparmurat Ataevich (First Secretary of the Soviet Communist Party's Central Committee) Обсуждение трудностей на пути осуществления реформы в сфере образования. В программе участвуют: Ниязов, Сапармурат Атаевич (Первый секретарь ЦК КПСС)